math

sqrt of x-1=x-3

square both sides. Gather terms, factor or use the quadratic equation. I will be happy to critique your work.

  1. 👍 0
  2. 👎 0
  3. 👁 89
asked by Jerry

Respond to this Question

First Name

Your Response

Similar Questions

  1. algebra

    Can someone please help me with this one? Solve (5x+4)^1/2-3x=0 Just so you know, it is to the 1/2 power. Add 3x to both sides of the equation, then square both sides. That should enable you to gather terms and factor. Yeah,

    asked by Lydia on March 10, 2007
  2. radical equation

    2^x+20=15+3^x A)1 B)16 C)-5 D)25 I chose c but i got it wrong i am having a problem understanding it. Let me rewrite the question in a more standard format. 2* sqrt(x)+20=15 + 3*sqrt(x) where * means multiply, and sqrt means the

    asked by jessica on June 29, 2006
  3. Math ,help

    how can i simplify this more its for the following problem: Problem #22 solve by using the quadratic formual. 5x^2-4x+1=0 this is where i am but i do not know how to go further. x = (4 (+/-) sqrt (-4))/(10) Problem #23 Solve by

    asked by jasmine20 on April 15, 2007
  4. Algebra2

    Find the polynomials roots to each of the following problems: #1) x^2+3x+1 #2) x^2+4x+3=0 #3) -2x^2+4x-5 #3 is not an equation. Dod you omit "= 0" at the end? #2 can be factored into (x+1)(x+3) = 0, so the roots are x=-1 and -3.

    asked by Haylee on May 13, 2007
  5. math,help,algebra I

    I need help can someone help me get unstuck and let me know if i am correct.thank you. solve by completing the square. 4x^2+2x-3=0 this is what i am doing: i used the quadratic equation. so where i am is in this step: x = (-2 (+-)

    asked by jasmine20 on April 14, 2007
  6. math

    (4-y^2)/(y-2) = y/2 (4-y^2)/(y-2) = y/2 4 - y^2 = (y*(y-2))/2 4 - y^2 = (y^2-2y)/2 8 - 2y^2 = y^2 - 2y 3y^2 - 2y - 8 = 0 (keep the above equation in mind) quadratic formula: (-b +/- sqrt(b^2 - 4ac))/2a now solve by plugging in the

    asked by math on October 30, 2006
  7. physics repost

    I am still trying to solve for H in this equation but I am still lost MgH = (1/2)*k*(H-2-10)^2 + Mg*2 I was told to expand the square on the right, gather terms, put it in the standard quadratic form, and use the quadratic

    asked by Chris Adison on April 24, 2008
  8. physics repost

    I am still trying to solve for H in this equation but I am still lost MgH = (1/2)*k*(H-2-10)^2 + Mg*2 I was told to expand the square on the right, gather terms, put it in the standard quadratic form, and use the quadratic

    asked by Chris Adison on April 24, 2008
  9. math,algebra

    can someone help me out factor out this 0=16t^2-122t+180 i have so far this but the last one i am not sure 8(2t^2-14t + ?) you need to use the quadratic formula: -b(+or-)[sqrt(b^2-4ac)/2a] so you are saying that i don't have to

    asked by jasmin20 on April 6, 2007
  10. Algebra

    Solve for s: h=(square root of 3)times s/2 and solve for h V= (pi)r squared h / 3 Solve for s: h=(square root of 3)times s/2 Multiply both sides by 2. 2h = (sqrt 3)*s*2/2 which cancels the 2 on the right. 2h = (sqrt 3)*s Now

    asked by Jamie on August 17, 2006

More Similar Questions